2015
DOI: 10.1111/cid.12349
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Loading of Dental Implants in Edentulous Mandibles by Use of Locator® Attachments or Dolder® Bars: Two‐Year Results from a Prospective Randomized Clinical Study

Abstract: Within the limitations of this study, results from immediate loading of two implants in the edentulous mandible with either Locator or bar attachments hardly differed. Prosthetic complications and aftercare measures in the Locator group were frequent but easy to handle. Ease of repair and cleaning, in particular, might be reasons for choosing the single-attachment system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
2
23
0
3
Order By: Relevance
“…The high number of maintenance interventions in the first year and the fifth year is, respectively, related to the high frequency of rebasing and repair in those years. The connection of the matrices in the dentures was realized indirectly during the fabrication procedure of the new IOD, instead of connecting with a rebasing or a direct connecting method as used in other studies (Kappel et al, ; Kleis et al, ; Mackie et al, ; Matthys et al, ). Since the cylindrical stud abutment (Locator) used in this study is a resilient attachment, the connection of the matrix under functional occlusal pressure, with uniformly distributed forces between attachment and supporting mandible, could explain these better results.…”
Section: Discussionmentioning
confidence: 99%
“…The high number of maintenance interventions in the first year and the fifth year is, respectively, related to the high frequency of rebasing and repair in those years. The connection of the matrices in the dentures was realized indirectly during the fabrication procedure of the new IOD, instead of connecting with a rebasing or a direct connecting method as used in other studies (Kappel et al, ; Kleis et al, ; Mackie et al, ; Matthys et al, ). Since the cylindrical stud abutment (Locator) used in this study is a resilient attachment, the connection of the matrix under functional occlusal pressure, with uniformly distributed forces between attachment and supporting mandible, could explain these better results.…”
Section: Discussionmentioning
confidence: 99%
“…The 30 subjects (nine female with mean age 69.64 ± 11.81 years and 21 male, mean age 68.67 ± 7.41 years) included in the study were selected from 46 edentulous patients who were dissatisfied with their new complete mandibular dentures and who participated in a randomized clinical trial (Kappel et al. ,b) after seeking implant treatment of the mandible at the Department of Prosthodontics of the University Clinic in Heidelberg. The inclusion and exclusion criteria for the initial study, and the study protocol for implant insertion and loading have been described elsewhere (Kappel et al.…”
Section: Methodsmentioning
confidence: 99%
“…; Kappel et al. ). A plethora of studies has revealed that implant‐supported mandibular overdentures improve subjective, i.e., patient‐based, outcomes, for example satisfaction with treatment and with oral health‐related quality of life (Emami et al.…”
mentioning
confidence: 98%
“…Reports on patient expectations at the beginning of the treatment are also scarce, and comparisons of subjective patient assessments of mandibular overdenture‐related variables that could support the use of 2 or 4 implants to support such dentures are not available. Importantly, little information is available about the effect of the attachments used on prosthetic complications and aftercare measures. In addition to bars, balls, and magnets, in recent years the unsplinted Locator ® attachment has been described . An implant‐retained overdenture on Locator ® attachments is a simple treatment option for the edentulous mandible and is associated with improved masticatory performance .…”
Section: Introductionmentioning
confidence: 99%